Functional status of reproductive system under treatment of silver nanoparticles in female mice - Lytvynenko, Alina P.; Rieznichenko, Ludmila S.; Sribna, Valentine A.; Stupchuk, Maria I.; Grushka, Nataliya G.; Shepel, Alena A.; Voznesenska, Tetyana Yu.; Blashkiv, Taras V.; Kaleynykova, Oksana N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The use of silver nanoparticles (AgNP) has increased very significantly in recent years the work in science is currently on focused on assessing human health and environmental risks of nanotechnology. The aim of the present study was to estimate the functional status of the female reproductive system in mice under condition of the intravenous treatment of silver nanoparticles (AgNPs), namely to assess meiotic maturation of oocytes, viability of follicular cells surrounding the oocyte, spontaneous contractile activity of the myometrium and pre-and post-implantation mortality of embryos. Methods: Research (two series) has been done on white laboratory mice (8 weeks, 16-18 g). AgNPs are spherical nanoparticles of 30 nm (8 mg/ml for metal) diluted in water for injection. Method of treatment: intravenous. Two doses (2 mg/kg and 4 mg/kg) have been investigated. Frequency of treatment: one time per day with each dose of 1, 5 and 10 times (n=10 animals in each group). Material for the study (ovaries, uterus) were taken the day after the last AgNPs injection. Results: Ten-time AgNPs treatment (2 mg/kg and 4 mg/kg) results in inhibition of oocytes meiotic maturation in mice; a single- and five-time AgNPs treatment (2 mg/kg and 4 mg/kg) increases the number of apoptotic cells, while the ten-time AgNPs treatment results in an increase of the apoptotic and necrotic follicular cells surrounding oocytes; for the five-and ten-time AgNPs treatment (4 mg/kg) the index of contractility (IC) of the uterus increased; for the ten-time AgNPs treatment (2 mg/kg and 4 mg/kg) no differences in value of the embryonic mortality between control and study groups have been observed. Conclusions: This study suggests that the development of nanomaterials should be safer and non-toxic and the potential reprotoxicity of AgNPs should be investigated more carefully.